Challenges and Advances in the Taxonomy of Deep-Sea Peracarida: From Traditional to Modern Methods - Frutos, Inmaculada; Kaiser, Stefanie; Pułaski, Łukasz; Studzian, Maciej; Błażewicz, Magdalena (Frontiers in Marine Science, 2022)
As one of the oldest branches of biology, taxonomy deals with the identification, classification and naming of living organisms, using a variety of tools to explore traits at the morphological and molecular level. In the deep sea, particular challenges are posed to the taxonomic differentiation of species. Relatively limited sampling effort coupled with apparent high diversity, compared to many other marine environments, means that many species sampled are undescribed, and few specimens are available for each putative species. The resulting scarce knowledge of intraspecific variation makes it difficult to recognize species boundaries and thus to assess the actual diversity and distribution of species. In this review article, we highlight some of these challenges in deep-sea taxonomy using the example of peracarid crustaceans. Specifically, we offer a detailed overview of traditional as well as modern methods that are used in the taxonomic analysis of deep-sea Peracarida. Furthermore, methods are presented that have not yet been used in peracarid taxonomy, but have potential for the analysis of internal and external structures in the future. The focus of this compilation is on morphological methods for the identification, delimitation and description of species, with references to molecular analysis included where relevant, as these methods are an indispensable part of an integrative taxonomic approach. The taxonomic impediment, i.e. the shortage of taxonomists in view of a high undescribed biodiversity, is discussed in the context of the existing large taxonomic knowledge gaps in connection with the increasing threat to deep-sea ecosystems. Whilst peracarid crustaceans are used here as an exemplary taxon, the methodology described has broad relevance to many other deep-sea taxa, and thus will support broader research into deep-sea biodiversity and ecology more widely.